Ze wzoru
kx-mx=d wylicz k
ax+c=d+bx wylicz x
Na szybko plis​


Odpowiedź :

[tex]Zadanie\\\\kx-mx=d\ \ \ \mid+mx\\\\kx=d+mx\ \ \ \mid:x\\\\k=\frac{d+mx}{x}\ \ \ \ \ lub \ \ \ \ \ k=\frac{d}{x}+m\\\\Zal.\\x\ne0\\\\ax+c=d+bx\ \ \ \mid-bx;\ -c\\\\ax-bx=d-c\\\\ x(a-b)=d-c\ \ \ \mid:(a-b)\\\\x=\frac{d-c}{a-b}\\\\Zal.\\a-b\ne0[/tex]

Odpowiedź:

kx - mx = d         wylicz k

kx = d + mx      /:x

k = d/x + m

ax + c = d + bx           wylicz x

ax - bx = d - c

x(a - b) = d - c       /:(a - b)

x = (d - c)/(a - b)

Szczegółowe wyjaśnienie: